Utilization of Palm Oil Waste into Liquid Smoke in Cellulose Commercial Starch Nano Fiber Composite as Antimicrobial Substances in the Manufacturing of Food Packaging - Siregar, Efrizal; Sinambela, Yusnia; Anwar, Khairil; Sinaga, Romel (KnE Engineering, 2024)
The high demand for plastic use today will result in environmental damage because the plastic that is widely used cannot be broken down. This plastic waste is dangerous for the sustainability of the food chain, pollutes water and soil, causes global warming, and causes air pollution. This research synthesizes a cellulose nanofiber composite with commercial starch in a 1:1 ratio with the influence of the addition of smoke liquid from palm oil waste. This research aims to process cellulose nanocomposite fibers combined with commercial starch and use them in biodegradable plastic by testing the effect of giving smoke liquid on the development of microbial substances in environmentally friendly biodegradable plastic food packaging. So the resulting product is expected to have the potential to reduce dependence on the use of synthetic plastic. This research aims to determine the optimum concentration of liquid acid from empty oil palm fruit bunches as an antimicrobial agent in the resulting bioplastic. The addition of liquid smoke changes the bioplastic properties of FTIR and XRD the attractive strength of bioplastic. The sample with the highest concentration of liquid smoke had the greatest tensile strength (2.34 MPa). The addition of liquid smoke concentration from empty oil palm shells showed a good inhibitory area for the development of bacillus cereus (10.8 mm). Keywords: liquid smoke, plastic biodegradable, food packaging, antimicrobial